ANALISIS TERHADAP UNDANG-UNDANG NOMOR 23 TAHUN 2011 TENTANG PENGELOLAAN ZAKAT (PERSPEKTIF HUKUM ISLAM) - Hakim, Budi Rahmat (Syariah: Jurnal Hukum dan Pemikiran, 2015)
The Birth of Law No. 23/2011 marks a new era of transformation of the national charity which has given rise to a new paradigm of charity management in our country. Some rules are the result of constitutive ijtihadin the ?eld of charity gets a reaction from some quarters, especially related to the management of charity by the state authority. Regardless of the debate which led to the material and formal lawsuit, there are several key issues to be further analyzed in relation to the reconstruction of ?qh paradigm evaluated from the perspective of contemporary Islamic law. First, the authorities and the involvement of the state as charities through the agency or institution that is of?cially established or recognized by the state, so that the management of charity can be done effectively, guaranteed. And have legal certainty. Secondly, the absence of sanctions for muzaki who shirk the obligation of charity in Law No.23 / 2011 shows that the payment of charity is voluntary, therefore charity regulations in Indonesia are still considered weak in the legal framework that can bind to the individual or business entity that is exposed to the taxpayer , Third, the reform paradigm of subject, object and charity tas{arruf ?eld have already accommodated in Law No.23 / 2011 in accordance with the principle of mas}lah}atand justice. Fourth, the relationship of charity and tax reaf?rmed in the amendment of new Law charity as?scal incentives for charity payers to make charity as a reduction of PKP (tax deduction), although this provision has not been able to realize the position of charitywhich is more signi?cant as a tax deduction(tax credit).